Inflation Expectations and Misallocation of Resources: Evidence from Italy - Tiziano Ropele; Yuriy Gorodnichenko; Olivier Coibion (Institute of Labor Economics (IZA), 2023)
Using Italian data that includes both inflation forecasts of firms and external information on their balance sheets, we study the causal effect of changes in the dispersion of beliefs about future inflation on the misallocation of resources. We find that as disagreement increases, so does misallocation. In times of low inflation, the aggregate TFP loss of the dispersed expectations-induced misallocation is moderate, but we argue that it likely becomes quite significant in times of high inflation.
Keywords: E31; C83; D84; O47; 330; misallocation; inflation expectations